Characterization of detailed features in high resolution satellite data for urban local plans in Malaysian perspectives - Hj. Mohd. Noor, Norzailawati; Hashim, Mazlan (2007)
The second generation of fine resolution satellite image has enable detailed features of importance to urban be extracted at relatively large scale. This information offers new opportunities for input into the urban spatial data infrastructure of many global cities, apart from also able to provide spectral information that when processed accordingly can derive intangible information of importance to urban environmental management. This article examines the opportunity and limitations of current fine resolution satellite data for producing of local plan at scale of 1:1500 at selected cities in Malaysia. Both the radiometric and geometrical features derived for the plan are also comprehensively evaluated for all related urban plan classes and the optimal derivation techniques is then mechanize for operational view point.